Simian rotavirus SA-11 plaque formation in the presence of trypsin. - Ramia, S (1979)
Incorporation of 5 micrograms of trpsin per ml of the overlay (Eagle minimal essential medium-0.7% Ionagar no. 2) was found to be necessary for plaque formation by simian rotavirus SA-11. Plaques of 3 to 4 mm in diameter were produced in MA-104 cells after 5 days of incubation at 37 degrees C. Plaque size was even larger (5 to 6 mm) in monolayers of African green monkey kidney cells. Addition of diethyl-aminotheyl-dextran, protamine sulfate, or 5-bromodeoxyuridine to the trypsin-containing overlay did not improve plaque formation by the virus. Incorporation of beef extract or yeast extract to a final concentration of 0.5% in the trypsin-containing overlay inhibited plaque formation. On the other hand, the presence of lactalbumin hydrolysate or peptone at a similar concentration in the overlay did not inhibit plaque formation. When methylcellulose was used instead of the agar as the solidifying agent in the overlay, no plaques were seen. SA-11 is a useful model for the study of human rotaviruses, and this relatively simple plaque assay system should further enhance its usefulness in this regard.